Experimental Study on Corrosion of Galfan-Coated Full-Locked Coil Ropes in a Natatorium Environment - Shi-Chang Zhang; Xiao-Ming Xu; Feng Gao; Bin Luo; Wei-Zhou Shi; Qing Fang (Advances in Civil Engineering)
Galfan-coated full-locked coil rope is widely applied in long-span spatial structures because of its high strength and lightweight. However, the corrosion problem is relatively serious in the natatorium, which affects the structure’s durability. To deeply reveal the corrosion mechanism of Galfan-coated cable, this study first measured the natatorium on-site, and the results indicated that the natatorium environment can be simulated by a constant temperature and humidity environment in engineering. Then, the constant temperature and humidity corrosion test was carried out to simulate the corrosion of Galfan-coated cable with a certain amount of chloride ions on the surface, and the early corrosion rate was obtained. Later, the neutral salt spray accelerated corrosion test was carried out to predict the corrosion rate of the cable in the natatorium environment in the middle and late periods. The specimens included no-stress unprotected coating cable, high-stress unprotected coating cable, and high-stress protected coating cable. The results show that high stress will accelerate the corrosion, and a protective coating can effectively prevent the corrosion. Finally, the linear model, bilinear model, and bilinear model considering chloride ion accumulation were proposed to study the corrosion of the Galfan coating. The results show that the linear model overestimates the corrosion rate, and the bilinear model and bilinear model considering chloride ion accumulation are practical. Meanwhile, corresponding maintenance suggestions were given for the natatorium project to improve the structure's durability.